Perbedaan Efektivitas Penggunaan Jenis Media Edukasi Tentang Anemia Terhadap Pengetahuan, Sikap, Efikasi Diri Remaja Putri Desa Sirnagalih - Alifah Safira Amperatmoko; Apriningsih Apriningsih; Feda Anisah Makkiyah; Widayani Wahyuningtyas (Jurnal Kesehatan Komunitas, 2022)
Efforts to prevent anemia in adolescent girls are very important to prevent the risk of abortion, low birth weight infant, the uterus cannot contract properly, bleeding after delivery which results in death. Furthermore, one of the efforts to prevent anemia in the field of health promotion is by using learning media as a form of educational activity regards to anemia. The aim of this study is that to determine the differences in the effectiveness of the use of educational media about anemia on the knowledge, attitudes, and self-efficacy of adolescent girls in Sirnagalih village. Moreover, this type of this study was quantitative with a quasi-experimental design – non-equivalent control design. The numbers of samples in this study were 60 people obtained by purposive sampling technique. The instruments used were pretest and posttest questionnaires. Meanwhile, the analysis used in this study was the Wilcoxon and Mann Whitney test. The results of the study after health education are conducted show that there is a difference in the level of knowledge, attitudes and self-efficacy of adolescents girls about anemia (p<0.005). The conclusion of the study shows that video media is more effective to be used as an educational medium about anemia for adolescents girls since based on statistical tests, the average value of video media is higher than the average value of poster media.